2015
DOI: 10.14202/vetworld.2015.918-923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding chayote (Sechium edule) meal on growth performance and nutrient utilization in indigenous pig (Zovawk) of Mizoram

Abstract: Aim:This study was planned to investigate the effect of feeding different levels of chayote (Sechium edule) meal by replacing standard concentrate mixture (CM) on the growth parameters such as feed intake, body weight gain, average daily gain (ADG) and feed conversion ratio (FCR), and nutrient utilization in indigenous pig of Mizoram.Materials and Methods:Twenty-four growing indigenous pigs (Zovawk) were used to study the effect of feeding chayote (Sechium edule) meal (fruits and leaves at the ratio 4:1) on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Both animals were fed chayote ( Sechium edule ) for a month as previously described and recommended [22]. Representative samples of total GI contents (500 mL) were collected immediately after slaughter.…”
Section: Methodsmentioning
confidence: 99%
“…Both animals were fed chayote ( Sechium edule ) for a month as previously described and recommended [22]. Representative samples of total GI contents (500 mL) were collected immediately after slaughter.…”
Section: Methodsmentioning
confidence: 99%
“…Chayote seems to play an important role in promoting growth in pigs, poultry and cattle or in their health management. Lalthansanga and Samanta (2015) studied the growth and nutrient utilization of Zovawk pigs fed on different levels of chayote meal (fruits and leaves) in the diet. After a 90-day feeding trial, it was found that chayote meal could safely replace the standard grower ration up to 40% in the diet of pigs without causing any adverse effects on growth and nutrient utilization.…”
Section: Animal Nutritionmentioning
confidence: 99%
“…In recent years, reports about chayote have been mainly related to the function, compositions, and applications of its fruit, stems, leaves, and tubers 4 , 9 , 15 , 16 . Although there has been extensive exploration of the genomes within the Cucurbitaceae family, such as Cucumis sativus (2 n = 2 x = 14, 226.2 Mb) 17 , Cucumis melo (2 n = 2 x = 24, 398.57 Mb) 18 , Citrullus lanatus (2 n = 2 x = 22, 353.5 Mb) 19 , Cucurbita pepo (2 n = 2 x = 20, 263 Mb) 20 , Luffa cylindrica (2 n = 2 x = 26, 656.19 Mb) 21 , Lagenaria siceraria (2 n = 2 x = 22, 313.4 Mb) 22 , and Benincasa hispida (2 n = 2 x = 24, 913 Mb) 23 , there is no complete genome of chayote available at present 24 , and there have only been a few studies on methods for chayote DNA extraction 25 and on the genes expressed in chayote fruit 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%